The effect of smear layer removal on E faecalis leakage and bond strength of four resin-based root canal sealers - Laura Andriukaitiene; Xiaobo Song; Nannan Yang; Lippo V. J. Lassila; Pekka K. Vallittu; Eero Kerosuo (BioMed Central, 2022)
Background: The aim of the study was to assess bacterial sealability and bonding ability of methacrylate-based Resilon (RS, SybronEndo), Endo Rez (ER, Ultradent Products Inc), and epoxy-based AH Plus (AH, Dentsply/DeTrey), MTA Fill Apex (MTAF, Angelus Solucoes Odontologicas) root canal sealers, and the effect of the smear layer removal on the sealability.
Methods: One hundred thirty root segments were instrumented up to apical size #60 and rinsed with 2.5% NaOCl. Half of the roots were rinsed with 5ml 17% EDTA to remove the smear layer. All the roots were filled with AH, ER, MTAF sealers and gutta-percha, or RS with Resilon cones. After storage at 37 degrees C for 7 days the samples were mounted into bacterial leakage assay for 50 days.
Another 100 roots were instrumented and rinsed as described above, split longitudinally, cut into the cervical, middle and apical parts. The sealers were injected through the plastic mould on the dentin surface. After 7 days of incubation at 37 degrees C, bond strength was tested using a notched-edge test fixture (Crosshead, Ultradent Products Inc.) and a universal testing machine (Lloyd Instruments).
Results: AH revealed the longest mean time for bacterial resistance by 29.4 and 36.8 days (with and without smear layer, respectively) followed by RS (15.1 and 24.7 days, respectively). The difference between materials was significant (p<0.001).
Bond strength values ranged from 0.2 0.1 to 3.5 +/- 0.7 MPa and increased from the apical to the cervical third. In the apical third, AH showed the highest mean (SD) bond values 1.4 (0.4) MPa and 1.7 (0.6) MPa (with and without smear, respectively, followed by RS, 0.5 (0.1) MPa and 0.8 (0.1) MPa, respectively. The difference between materials was significant (p=0.001).
Conclusion: The effect of the smear layer removal on the sealability was material-dependent.